Defining Operational Equivalent of Classic and Combination-Information Mental Function of Prospective Science Teacher Knowledge of Electricity Procedural Knowledge Subject by Comparing Theoretical and Experimental Data - İsmail Yılmaz (Sakarya University Journal of Education)
By comparing theoretical and experimental data, we aim to improve the learning and mental functions of prospective science teachers. Accordingly, mental function operations are defined by a qualitative study to ensure the establishment of a “bijective mental” level. Combination-information (CI)-level intervals of mental function operations are determined by knowledge and success. These are defined by the relation between the procedural knowledge in the cognitive domains of solutions and possible cases of data (questions) through an assessment tool. This tool includes open-ended questions for assessing the procedural knowledge of electricity of prospective science teachers. By employing these level intervals and comparing the obtained CI knowledge and success levels through problem-solving, the CI mental function operation equivalencies of prospective-teacher knowledge levels of electricity are established. To determine the equivalencies of classic mental function operations, an equal level interval is used. By comparing classic knowledge and success levels with these interval values, classic mental function operation equivalencies are determined. Using these equivalencies, learning and mental functions are improved. Based on the results, we provide suggestions on maintaining bijective mental levels.